A Replication and Analysis of Tiebout Competition Using an Agent-Based Computational Model. (April 2015) - Seagren, Chad W.
Replication is a critical element of the scientific process. This article is an effort to contribute to the slowly growing literature concerning the replication of agent-based computational models. We present a replication of Kollman, Miller, and Page's model of Tiebout sorting. In that model, individual agents with heterogeneous preferences for government policies select among jurisdictions that offer the most satisfactory package of government services. This project makes three contributions to the literature. First, our successful replication provides the research community with a modernized version of that seminal model. Second, we confirm that earlier results with respect to the single jurisdiction setting are highly robust with respect to voter preferences, while the results for multiple jurisdiction settings are more sensitive. Finally, we demonstrate a technique for conducting sensitivity analyses that leverages a high-dimensional experimental design.